Key Stakeholder Perceptions on the Future Human Resource Management Roles and Competencies - Jolkkonen, Karoliina (My University, 2013)
The HR roles and competencies are changing due to the increasingly volatile global business environment and the shift to a knowledge economy. Hence, clarity is needed regarding the HR roles and competencies in order to enable the HR organisation to respond to the future challenges faced by human resource management. The purpose of this study was to investigate the key stakeholder perceptions on the future HR roles and competencies in Finland. The focus was on the HR departmental roles and the competencies that HR professionals need for performing these roles. Comparisons between different individual, organisational and contextual level factors were also made to provide a pluralistic approach to the topic. These factors included different respondent roles, organisational types and levels of internationalisation. This research project was conducted through a survey strategy based on the material from a nationwide HR Barometer. The sample was analysed based on an existing HR role and competency typology and current HRM trends with a content analysis method. The main theoretical contribution of this study is a modified future HR role and competency model created based on the findings. This new typology includes three expanded HR department roles with an added competency category each. Credible activist needs to now also protect the long-term perspective, HR innovator and integrator provides smooth HR service delivery, and capability builder focuses on more traditional competencies in supportive and operational HRM. HR managers can utilise these research findings by focussing on the development of the highest rated HR roles and competencies first and by studying the circumstantial factors relevant to their organisation in order to be able to make more informed decisions.
Keywords: HRM; HR department roles; HR professional competencies; future HRM; HR typologies; fi=Master's Degree Programme in International Business|